Modeling the reduction of urban excess heat by green roofs with respect to different irrigation scenarios. (March 2018) - Heusinger, Jannik; Sailor, David J.; Weber, Stephan
Abstract: Urban heat reduction by evaporative cooling from extensive green roofs is explored by applying irrigation scenarios to green roofs located in different climate zones using a coupled atmosphere-vegetation-substrate green roof model. The model, which is integrated in the building energy simulation software EnergyPlus, is validated with eddy covariance surface energy fluxes from a green roof in Berlin, Germany. The original model was modified to include interception and an improved runoff calculation. Three irrigation scenarios were defined (no irrigation, sustainable irrigation by harvested runoff water, unrestricted irrigation) to study the heat reduction potential in terms of surface energy partitioning and sensible heat fluxes (QH ). The irrigation scenarios are compared to two white roofs (albedo equal to 0.35 and 0.65) and a black roof. High correlation of sensible and latent heat (QE ) fluxes between measured and modelled data for the original and the modified version of the green roof model were observed (for the original model, R 2  = 0.91 and 0.81 for QH and QE, respectively, while for the modified version R 2  = 0.91 and 0.80, respectively). The modified version was applied to study irrigation, due to lower systematic errors for QH, QE and better performance for the substrate moisture content. In comparison to a black roof the green roof reduces urban excess heat by 15%–51% with sustainable irrigation, by 48%–75% with unrestricted irrigation, but drops to 3% for unirrigated roofs in the different cities. Sustainable irrigation can be effective in climates with high annual (or summerly) precipitation. Highlights: First in-depth validation of EnergyPlus green roof model. Analysis of urban heat reduction potential of green roofs during hot periods. Irrigation improves the urban heat reduction of green roofs effectively. Sustainable irrigation is effective in climates with high precipitation.